Alcoholism and its Effects on the Central Nervous System - Mukherjee, Sukhes (Current Neurovascular Research, 2013)
Alcohol abuse is a major health problem worldwide, resulting to extensive admissions in many general hospitals. The overall economic cost of alcohol abuse is enormous worldwide. As a small molecule, alcohol can easily cross membrane barriers and reach different parts of the body very quickly. Attainment of its equilibrium concentration in different cellular compartments depends on the respective water content. Alcohol can affect several parts of the brain, but, in general, contracts brain tissues, destroys brain cells, as well as depresses the central nervous system. Excessive drinking over a prolonged period of time can cause serious problems with cognition and memory. Alcohol interacts with the brain receptors, interfering with the communication between nerve cells, and suppressing excitatory nerve pathway activity. Neuro-cognitive deficits, neuronal injury, and neurodegeneration are well documented in alcoholics, yet the underlying mechanisms remain elusive. The effect can be both direct and/ or indirect. In this review we highlighted the role of alcoholism on the CNS and its impact on human health.
Keywords: cns